The Impact of Gadget Addition on the Emotional Stability of Adolescents - Himatussa’adah; Rakhmawati, Dini; Julijatiningsih, Yovita (Universitas Mercu Buana Yogyakarta, 2026)
This study aims to determine the effect of gadget addiction on the emotional stability of tenth-grade students at Sultan Agung 1 Islamic High School, Semarang. The research employed a quantitative correlational design involving a sample of 83 students who were selected to represent the population. Two primary instruments were used in data collection, namely a gadget addiction questionnaire and an emotional stability scale, both of which were developed to measure students’ tendencies in using gadgets excessively and their ability to regulate emotions in daily life. Data were analyzed through descriptive statistics and simple linear regression, preceded by prerequisite tests including normality and linearity assessments. The results of the descriptive analysis indicated that the average score for gadget addiction was 73.70, which falls into the moderate category, while the emotional stability score averaged 71.84, categorized as high. Furthermore, the simple linear regression analysis revealed that gadget addiction contributed 50.6% to the variation in emotional stability, demonstrating a substantial influence. These findings suggest that although students’ emotional stability remains relatively good, excessive gadget use poses a significant risk factor for emotional decline. Therefore, the study highlights the crucial role of parents and schools in monitoring, guiding, and limiting students' gadget use to maintain their emotional well-being.